Diplomatic Divide - Khan, Humayun, Dr.; Edited By Page, David (New Delhi Lotus Collection, 2004)
Personal experiences of two senior retired diplomats who have served as ambassadors.
Keywords: Pakistan -- India -- Diplomatic relations